Micromobility Adoption in an Urban Heritage City: Insights from Young Tourists in George Town, Penang - Abdul Kadir, Irhanida; Woo, Yee Nee (Journal of Social Transformation and Regional Development, 2026)
As heritage urban centres face increasing challenges related to congestion, pollution, and accessibility, micromobility solutions have emerged as promising alternatives, particularly among younger demographics. This research employed a causal research design to assess the factors influencing micromobility adaptation among young tourists in George Town, Penang. Among the factors are perceived benefit, cost saving, environment motivation and perceived social norms. 200 sample size were used for this research. Data on socio-demographic characteristics were analysed descriptively, while the evaluation of the measurement model was done through multiple regression analysis. Findings from this study aimed to provide valuable insights for policymakers, urban planners, and micromobility service providers seeking to promote sustainable transportation solutions within heritage sites and urban environments. By understanding the unique needs and preferences of youngsters, strategies can be developed to enhance the accessibility, affordability, and attractiveness of micromobility options, thereby fostering more inclusive and environmentally sustainable transportation systems in George Town and other heritage cities. The results indicate that while perceived advantages do not notably affect the adoption of micromobility, factors such as cost savings, perceived social norms, and environmental motivation play a significant role. The study underscores the importance of overcoming obstacles to micromobility adoption and fostering environmental consciousness to facilitate the integration of micromobility into urban transportation systems. Additionally, policymakers can utilise these findings to develop focused approaches aimed at enhancing micromobility integration, thus promoting environmental sustainability and preserving cultural heritage in Penang.